Analysis of Tenth-Year Students' Eating Habits of a Technical High School in Pérez Zeledón Based on the Transversal Themes of the Program for Third Cycle of Costa Rica Basic General Education - José Miguel Pereira-Chaves; María de los Ángeles Salas-Meléndez (Universidad Nacional, Costa Rica, 2017)
The objective of this study was to diagnose the knowledge tenth-grade students have about eating habits and nutrition. This analysis reviews the relation between good nutrition and the transversal axes of the program of study for the third cycle of Costa Rica's general basic education. Considering that healthy eating should not escape from the educational field, the nutritional values and eating habits should be inculcated to students, so that they can develop optimally in life. A survey containing 13 items with open and closed multiple-choice answers was applied to 30 tenth-grade students, and 18 teachers from a Professional Technical High School located in Pérez Zeledón, San José, Costa Rica. The main results showed the poor nutritional culture of the surveyed students in this educational center, and the lack of commitment of the teachers to mainstream healthy eating habits in their classes.